#TITLE_ALTERNATIVE# - PUTRA NUGROHO (NIM 13205013), ANDIKA
This final project implemented DSP based ANC for attenuate noise that caused by recorded car's machine. Experiments were done in small enclosure using multichannel feedforward FxLMS algorithm. Optimization on geometrical positions of sensors and noise cancelers were done. The experimental results show that the optimal geometric position is where the canceler source is place close to primary noise. Maximum attenuation with 64 order of filter is 3,5 dBA. More filter order makes ANC better, with 128 order of filter, attenuation achieved at 4 dBA. However DSP capability limits the length of filter order, cause it takes longer time to calculate longer order.